Evaluation of apramycin against spectinomycin-resistant and -susceptible strains of Neisseria gonorrhoeae - Riedel, Stefan (J Antimicrob Chemother, 2019)
BACKGROUND: The emergence of Neisseria gonorrhoeae resistant to all currently available antimicrobial therapies poses a dire public health threat. New antimicrobial agents with activity against N. gonorrhoeae are urgently needed. Apramycin is an aminocyclitol aminoglycoside with broad-spectrum in vitro activity against MDR Gram-negative pathogens and Staphylococcus aureus. However, its activity against N. gonorrhoeae has not been described. OBJECTIVES: The activity spectrum of apramycin against a collection of MDR N. gonorrhoeae was assessed. Isolates tested included those susceptible and resistant to the structurally distinct aminocyclitol, spectinomycin. RESULTS: The modal MICs for apramycin and spectinomycin were 16 mg/L and 32 mg/L, respectively. The epidemiological cut-off (ECOFF) for apramycin was 64 mg/L. No strains among 77 tested had an MIC above this ECOFF, suggesting very low levels of acquired apramycin resistance. In time–kill analysis, apramycin demonstrated rapid bactericidal activity comparable to that of spectinomycin. CONCLUSIONS: Apramycin has broad-spectrum, rapidly bactericidal activity against N. gonorrhoeae. Future pharmacokinetic and pharmacodynamic studies will be needed to determine whether apramycin and/or apramycin derivatives hold promise as new therapeutics for N. gonorrhoeae infection.